64. Comparison of the effects of topical and intravenous administration of tranexamic acid on postoperative blood loss in single-level posterior lumbar interbody fusion - Kitaguchi, Kazuma; Kaito, Takashi; Wada, Eiji (North American Spine Society journal (NASSJ), 2024)
Tranexamic acid (TXA), a synthetic antifibrinolytic drug, competitively blocks the lysine-binding sites of plasminogen, plasmin, and tissue plasminogen activator, thus reducing bleeding. Intravenous TXA has been used to effectively reduce perioperative blood loss in spinal surgery. However, high-dose intravenous TXA may cause complications, such as seizures, deep vein thrombosis (DVT), and pulmonary embolism (PE). In contrast, topical TXA has been used to avoid the risk of such complications and has shown efficacy in reducing total blood loss in spine surgery. Topical TXA has a similar hemostatic efficacy to intravenous TXA. However, whether intravenous or topical TXA is more effective in reducing postoperative bleeding in spine surgery remains unclear. This study aimed to compare the efficacy and safety of topical and relatively high-dose intravenous tranexamic acid (TXA) in reducing postoperative blood loss in patients undergoing single-level posterior lumbar interbody fusion (PLIF). The same timing of administration was used for both formulations. This study was a nonrandomized case-control study. A total of 120 patients diagnosed with single-level degenerative lumbar disease underwent single-level PLIF at our hospital between 2016 and 2023. The primary outcome was postoperative blood loss, which was evaluated by measuring the output from the suction drain. Secondary outcomes included estimated total perioperative blood loss, hemoglobin (Hb) level, hemoglobin variations (Hbv), and incidence of allogeneic blood transfusion. The total perioperative blood loss was calculated using Hbv. Hbv (g/dL) were calculated from before surgery to POD4 and POD7, and the lower of the two values was included in the analyses. A total of 120 patients were retrospectively enrolled and assigned to three groups: (a) control group, which received no TXA; (b) TXA (iv) group, which received intravenous administration of a relatively high dose (2 g) of TXA immediately before wound closure; and (c) TXA (t) group, which received topical application of TXA (1 g in 100 mL saline solution) to the wound immediately before wound closure. The drain was released 20 minutes after topical or intravenous TXA administration. A total of 120 patients were included in the study: control group, n = 60; TXA (iv) group, n = 30; and TXA (t) group, n = 30. Total postoperative blood loss was significantly lower in the TXA (t) group than in the TXA (iv) and control groups (350.8±132.6 vs 566.4±178.8 vs 704.4±225.9, respectively; both p<0.01, unit: ml). Analysis of blood loss over time showed significantly less blood loss throughout the postoperative period in the TXA (t) group compared with the control group; in contrast, the TXA (iv) group showed less blood loss than the control group only in postoperative hours 2 to 6. The Hbv value and total perioperative blood loss were significantly lower in the TXA (t) group than those in the control and TXA (iv) groups. No complications, including thromboembolic events, were associated with the use of either TXA formulation. After single-level PLIF, topical TXA shows rapid and long-lasting effects in reducing postoperative blood loss compared with twice the amount of intravenous TXA. This abstract does not discuss or include any applicable devices or drugs.